1996
DOI: 10.2519/jospt.1996.23.3.194
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Wearing Multifocal Lenses With Head Posture and Pain

Abstract: P osture is a "composite of the positions of all the joints of the body at any given moment" (8). Poor posture results in muscle imbalances with concomitant muscle shortening or elongation. These changes in muscle length will result in a faulty relationship between the various parts of the body, producing increased strain and decreased eficiency of the body (9,l2,15).Three major factors influence adult posture: I) heredity, 2) disease, and 3) habit. Physical therapeutic intervention attempts to alleviate sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…In addition, Szeto et al [33] found that a small sample of women with neck and shoulder pain showed trends towards having increased head tilt and neck flexion postures during computer work as compared to asymptomatic women. Most recent research has, however, indicated that this supposed association between head posture and pain does not necessarily exist [37,12,39]. Head posture while sitting appears to be time-and task-dependent.…”
Section: Introductionmentioning
confidence: 81%
“…In addition, Szeto et al [33] found that a small sample of women with neck and shoulder pain showed trends towards having increased head tilt and neck flexion postures during computer work as compared to asymptomatic women. Most recent research has, however, indicated that this supposed association between head posture and pain does not necessarily exist [37,12,39]. Head posture while sitting appears to be time-and task-dependent.…”
Section: Introductionmentioning
confidence: 81%
“…However, it is cumbersome and inconvenient to use in clinical practices. Previous studies demonstrated that associations exist among FHP, neck pain, and disability [4][5]9,16,20]. The studies found that subjects with head, neck, and shoulder discomfort are more likely to have a smaller CV angle that indicates an FHP than that of asymptomatic subjects.…”
Section: Introductionmentioning
confidence: 98%
“…Proper posture maintains the musculoskeletal balance equilibrium [4], and poor posture might result in muscle imbalance that causes a faulty relationship among various body parts [5]. Forward head posture (FHP) is one of the most common cervical abnormalities that predisposes individuals toward pathological conditions, such as headache [6][7], neck pain [8][9], temporomandibular disorders [10], vertebral bodies disorders [11], soft-tissue length and strength alteration [12][13], or even scapula and shoulder dyskinesis [14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The neck posture adapted during a computer task suggests that there is a greater degree of forward head posture among multifocal lens wearers when compared to nonmultifocal lens wearers. According to Willford et al (1996), an interaction between forward head posture and pain was postulated by sustained sitting for many hours. Unnatural positions may lead to musculoskeletal discomfort and ergonomics concerns.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%